Genética de la resistencia a bacteriosis comén en frijol tepari - Urrea, C.=700 1 Milklas, P.; Beaver, J.; Zapata, M.
Sumarios (Es, En)
20 ref.
Keywords: PHASEOLUS ACUTIFOLIUS; BACTERIOSIS; RESISTENCIA A LA ENFERMEDAD